Review of Exhibiting Irishness: Empire, Race, and Nation, c. 1850-1970, by Shahmima Akhtar - Lauren Alex O'Hagan (Review of Irish Studies in Europe)
Review of Exhibiting Irishness: Empire, Race, and Nation, c. 1850-1970, by Shahmima Akhtar (Manchester: Manchester University Press, 2024), 264 pp., ISBN: 9781526157263, £85 (hardcover)